2018
DOI: 10.1159/000494792
|View full text |Cite
|
Sign up to set email alerts
|

Salusin-α Inhibits Proliferation and Migration of Vascular Smooth Muscle Cell via Akt/mTOR Signaling

Abstract: Background/Aims: The proliferation and migration of vascular smooth muscle cells (VSMCs) are key steps in the progression of atherosclerosis. The aim of the present study was to investigate the potential roles of salusin-α in the functions of VSMCs during the development of atherosclerosis. Methods: In vivo, the effects of salusin-α on atherogenesis were examined in rabbits fed a cholesterol diet. The aortas were en face stained with Sudan IV to evaluate the gross atherosclerotic lesion size. The cellular comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…24,26 It was also demonstrated that decreasing the levels of phospho-Akt and phospho-mTOR proteins in VSMCs reduce the aortic lesion areas of atherosclerosis in rabbits. 27 Taken together, these studies highlight the importance of developing new effective therapeutic strategies to inhibit cardiovascular remodelling to improve the prognosis in the management of patients with hypertension and other cardiovascular diseases.…”
Section: Angii-mediated Cardiovascular Remodelling Signalling Cascamentioning
confidence: 98%
“…24,26 It was also demonstrated that decreasing the levels of phospho-Akt and phospho-mTOR proteins in VSMCs reduce the aortic lesion areas of atherosclerosis in rabbits. 27 Taken together, these studies highlight the importance of developing new effective therapeutic strategies to inhibit cardiovascular remodelling to improve the prognosis in the management of patients with hypertension and other cardiovascular diseases.…”
Section: Angii-mediated Cardiovascular Remodelling Signalling Cascamentioning
confidence: 98%
“…Cell migration was detected using a wound-induced migration assay [18]. In brief, A549 cells were seeded in 6 well plates at 1×10 5 cells/well.…”
Section: Cell Migration Assaymentioning
confidence: 99%
“…The antiinflammatory effect is also related to the inactivation of the Akt/mTOR pathway and the inhibition of the secretion of IL-1β induced by lipopolysaccharide. Therefore, induction of macrophage autophagy can be a potential therapeutic strategy for AS [50].…”
Section: Macrophage-based Therapy Strategiesmentioning
confidence: 99%